Is Antibiotic Prophylaxis Necessary in Mastectomy with Antimicrobial Sutures? A Comparative Analysis - Pajaanti, Samuli; Oranges, Carlo M.; di Summa; Pietro Giovanni; Giordano, Salvatore (MDPI, 2026)
Background/Objectives: Surgical site infection (SSI) rates following breast surgical procedures range from 0.8% to 26%. Both prophylactic antibiotics and antimicrobial-coated sutures have been shown to play an important role in reducing these complications. This study aimed to evaluate the impact of antibiotic prophylaxis in mastectomy procedures using triclosan-coated sutures.
Methods: This study included 300 consecutive patients who underwent mastectomy for breast cancer over a two-year period, during which triclosan-coated Vicryl Plus sutures were used. Patients were divided into two groups based on the use of antibiotic prophylaxis. The prophylaxis group received 1.5 g cefuroxime intravenously at anesthesia induction (600 mg clindamycin in case of allergy), while the control group received no antibiotics. Endpoints of interest included differences in SSI and specific wound-healing complications at follow-up.
Results: There was no significant difference in the overall SSI rates between the two groups: 23.2% in the prophylaxis group vs. 18.8% in the control group [odds ratio (OR): 0.88; 95% confidence interval (CI): 0.69–1.13; vs. OR: 1.16; 95% CI 0.85–1.58; p = 0.343]. No adverse drug reactions were observed. Staphylococcus aureus was the most isolated microorganism in both groups. Multivariate analysis identified prolonged operative time and hematoma formation as significant predictors of postoperative infection.
Conclusions: Antibiotic prophylaxis did not reduce the rate of SSI following mastectomy for breast cancer when triclosan-coated sutures were used. Further high-quality, independent studies are warranted, particularly in breast surgery context.